2020
DOI: 10.1177/1045389x20932212
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, crystallinity, mechanical properties, and shape memory behavior of polyurethane/hydroxyapatite nanocomposites

Abstract: Herein, polycaprolactone diols with diverse molecular weights were synthesized by ring-opening method. Then, polyurethanes were synthesized through two-step pre-polymerization method by polyaddition of hydroxyl and –NCO groups. Afterward, a set of polyurethanes/hydroxyapatite nanocomposites were synthesized through solution casting as well as in situ polycondensation methods. The exact nominal molecular weights of the synthesized polycaprolactones were determined by proton nuclear magnetic resonance (hydrogen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The crystallinity degree (DC) of polyurethane composites shown in Table 3 confirmed that the inclusion of AL-N and AL-Z in polyurethane matrices reduced the crystalline regions due to the disruption of interactions inside soft segments. Marand et al [ 72 ] obtained analogous results with the inclusion of hydroxyapatite nanoparticles in polyurethane matrices with PCL-diol.…”
Section: Resultsmentioning
confidence: 65%
“…The crystallinity degree (DC) of polyurethane composites shown in Table 3 confirmed that the inclusion of AL-N and AL-Z in polyurethane matrices reduced the crystalline regions due to the disruption of interactions inside soft segments. Marand et al [ 72 ] obtained analogous results with the inclusion of hydroxyapatite nanoparticles in polyurethane matrices with PCL-diol.…”
Section: Resultsmentioning
confidence: 65%
“…The relative intensity of ester carbonyl vibration bond was used to determine the hydrogen bonding index, HBI. Hydrogen‐bonded and non‐hydrogen‐bonded bands were investigated by Peakfit software and HBI (C = O) was calculated using Equation 28 : HBI()Cgoodbreak=O=AC=ObA()Cgoodbreak=Ob+A()Cgoodbreak=Oitalicnb×100 where A()C=Ob and A()C=Oitalicnb denote the free and bonded carbonyl groups' peak area, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The relative intensity of ester carbonyl vibration bond was used to determine the hydrogen bonding index, HBI. Hydrogen-bonded and nonhydrogen-bonded bands were investigated by Peakfit software and HBI (C = O) was calculated using Equation 1 28 :…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…In bone tissue reconstruction, biomaterial choice is a key step to design and produce materials with great biodegradability and bioactivity 81 . Modern techniques to fabricate tissue cells outside the body human have been presented by researchers as inborn imperfections and harsh bone damage that are not easy to heal and their reproduction chance is not high.…”
Section: Hydroxyapatite‐based Smpu Nanocompositesmentioning
confidence: 99%